Alkaloids from some of the Malaysian annonaceae - Mohd. Sharif, Atan (1989)
Three known alkaloids,wilsonirine,O-methyldauricine and popisonine,and a new bisbenzylisoquinoline alkaloid have been isolated from Popowia pisocarpa and their structure have been fully characterized by spectral methods. Phaeanthus opthalmicus has yielded 0-methyldauricine and limacine as two major alkaloids.